ACCOUNTING AS A MEETING POINT BETWEEN INTERESTS OF STATE AND BUSINESS - Sapozhnikova N.G.; Nikulkina I.V.; Lyalkova E.E.; Negashev E.V.; Brovkina N.D. (Scientific Journal of Pedagogy and Economics, 2020)
Accounting is one of the main management functions along with functions such as planning, regulation, organization and incentives. This means that improving management and creating a market mechanism are inextricably linked with the development of the entire accounting system. The priority area for using the information generated in the accounting system is meeting the needs of a certain circle of interested parties. Accounting, by virtue of its constituent elements and methods of maintenance, is an information system that gives its internal and external users a complete picture of financial and economic activities. Russian accounting is traditionally focused on tax legislation, and the problem arises of the need to keep records for both tax authorities and for the purposes of the financial market. The globalization processes taking place in the global system have a significant impact on the formation of various concepts, including accounting concepts. Due to the main objective and subjective factors - liberalization and increased competition in the national markets of developed countries, improving the technology of financial accounting operations, the overall growth of world production - economic globalization processes have become possible. The problem of accounting unification is one of the main ones in the global economy. The state’s interest in expanding the scope of export-import operations, selling shares and securities on exchanges of different countries, in attracting foreign capital to the country stimulates the processes of standardization and unification of accounting processes and principles, bringing them into line with international standards, which is necessary to facilitate understanding of financial user reports from different countries. In the case when the primary interests of the state affect domestic policy issues, the accounting and reporting system is formed under the influence of the needs of national lenders and investors, reflecting the principles and concepts adopted in this country. Accounting is considered as an area of coordination of interests of the state and business in the context of globalization of the global economy. Globalization has led to the fact that many aspects of accounting as a scientific discipline and practical activity have acquired international coloring, while accounting has not yet been taken to a new level of the methodology used in the global system. It is necessary to follow uniform rules for accounting, calculating financial results and preparing financial statements, which will ensure sufficient transparency of the reporting data, their understanding and unambiguous interpretation in the international context. Theory of accounting is a combination of diverse concepts, united by the laws and specifics of the requirements and goals of users of information generated in accounting as a set of directions, trends and schools that explain the accounting process from their methodological positions. The current state of accounting theory does not meet the requirements of its reform. First of all, the tasks adopted by the Concept for the Development of Accounting and Reporting in the Russian Federation cannot be solved by methods accepted in theory. Accounting requires a revision of goals, reformulation of approaches to the presentation of basic theoretical principles. Modern theory has not yet been able to find effective solutions to pressing problems of accounting during its reform in connection with the transition to IFRS. When developing the theory of accounting, information from new areas of economic life (stock market, insurance, investment, bankruptcy, etc.) is practically not taken into account, the problem of reconciling the diverse interests of users of accounting